Alliance Dilemma with the U.S. and the Reconceptualization of Japanese Pacifism - Velicia Faustine Halim; Idil Syawfi (Parahyangan Center for International Studies, 2020)
This paper aims to explain the alliance dilemma between the United States and Japan and its impact on the reconceptualization of Japanese pacifism. It implies a decline in one-country pacifism intensity and increasingly flexible reinterpretations of Article 9. Through this research, it turns out that Japan’s lower position of bargaining leverage than the U.S. and the risk of entrapment in alliance dilemma between the U.S. and Japan affect the reconceptualization of pacifism in Japan. The conclusion draws on the findings through the theoretical framework of Glenn Snyder’s Alliance Dilemma, with James D. Morrow’s concept of Autonomy and Security. The term ‘alliance dilemma’ refers to two possible choices states could pick to avoid certain risks in the alliance: “C” strategy (to cooperate) or “D” strategy (to defect). The analysis reveals that Japan is more inclined to choose “C” strategy since it is very dependent on the U.S. As the bad prospective in “C” strategy eventually comes into effect, Japan’s lower position of bargaining leverage than the U.S. and the risk of entrapment it bears become the reasons of reconceptualization of its pacifism.